A Banyan Tree - (:unkn) unknown (The Bonanza, Smith Bros and Co., Port of Spain, Trinidad, 2009)
A picture of a man standing next to a Banyan Tree (Ficus benghalensis), also known as Indian fig.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Ficus benghalensis; Banyan tree--Trinidad and Tobago